Economic Inequality Decomposition and Spatial Pattern of Crime in Indonesia. (3rd July 2022) - Widyastaman, Putu Angga; Hartono, Djoni
Abstract: Rising crime victimization rate in Indonesia shows that crime is still a serious problem in the country. This study aims to identify the relationship between economic inequality and crime rate in Indonesia. It used the decomposed Theil indices, as the measure of inequality based on national household survey panel data, to disentangle the effect of economic inequality into within-district/city and between-district/city economic inequality components. This choice of inequality measure is due to the fact that most of the previous studies regarding economic inequality and crime overlooked the disentanglement between economic inequality effects. Another problem addressed by this study is that the effect of crime is not bounded by administrative boundaries. A high prevalence of crime in a region may cause a criminal spillover to the surrounding regions. To control for this effect, this study also evaluates the spatial effect of interregional crime rates using the panel spatial autoregressive model as the estimation method. The estimation results revealed that both within-region and across-region economic inequalities have substantial increasing impacts on the crime rate.